Transformasi Model Evaluasi Pembelajaran Berbasis Teknologi Di Era Society 5.0 - Soraya, Fina; Marzuki, Ismail (Universitas Muhammadiyah Tangerang, 2024)
This research addresses the issue of transforming learning evaluation models to be more aligned with the demands of Society 5.0, where technology integration plays a crucial role. The study aims to explore and analyze the adaptation of technology-based evaluation models in educational settings, highlighting their effectiveness and challenges. Utilizing a descriptive qualitative research method, data were collected through interviews with educators, document analysis, and observations in various educational institutions. The study found that while the integration of technology in evaluation processes has the potential to enhance learning outcomes and provide more accurate assessments, there are significant challenges related to the readiness of both educators and students, as well as infrastructure limitations. The findings underscore the need for continuous professional development for educators, investments in educational technology, and a more nuanced understanding of the diverse needs of learners in this new era. The research contributes to the ongoing discourse on educational innovation and the necessity of evolving evaluation models to meet the expectations of Society 5.0.Keywords: learning evaluation, learning process, and learning application